2022
DOI: 10.1186/s43093-022-00173-1
|View full text |Cite
|
Sign up to set email alerts
|

Board of directors and earnings manipulation: evidence from regulatory change

Abstract: The purpose of this paper is to examine the effect of the board of directors’ related clauses such as independence, female director, CEO Duality and the expertise of director included in the Code of Corporate Governance 2017 (CCG-2017) on earnings management with the pre- and post-CCG-2017 analysis. This study has used the sample of 323 non-financial listed firms of the Pakistan Stock Exchange from 2015 to 2019. Data were manually collected from companies’ annual reports, and two proxies of earnings management… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 60 publications
3
16
1
Order By: Relevance
“…According to Zalata et al (2018), financial expertise helps directors understand the complex nature of financial statements, understand auditors' opinions, and support the auditor in the event of any dissension between management and the auditor. Consistent with previous studies such as (Khan and Kamal, 2021;Qiao et al, 2018;Siam et al, 2014;Zalata et al, 2018), the findings of this study indicate that having financially expert directors reduces EM in Pakistan.…”
Section: Regression Analysissupporting
confidence: 92%
See 1 more Smart Citation
“…According to Zalata et al (2018), financial expertise helps directors understand the complex nature of financial statements, understand auditors' opinions, and support the auditor in the event of any dissension between management and the auditor. Consistent with previous studies such as (Khan and Kamal, 2021;Qiao et al, 2018;Siam et al, 2014;Zalata et al, 2018), the findings of this study indicate that having financially expert directors reduces EM in Pakistan.…”
Section: Regression Analysissupporting
confidence: 92%
“…Moreover, the results of Table 9 depict that financially expert director(s) is/are instrumental in reducing EM. This finding is in line with the results of Khan and Kamal (2021), who found that having professional (financially expert) and past-working experience directors on company boards reduces EM. These results corroborate and validate the agency theory hypothesis.…”
Section: Regression Analysissupporting
confidence: 91%
“…Pakistan is an emerging market with the features of a code-law country, but it is a common-law country. It has a less developed and unstable capital market, poor investor protection and a weak regulatory structure (Khan et al , 2022a). The listed firms on the PSX are mostly family-owned (Hussain, 2019), highly concentrated listed firms and more than 50% of the listed non-financial firms on the PSX are FBG-affiliated firms (Khan and Kamal, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, the FBG has a complex pyramidal ownership structure, including cross-directorship and cross-holdings, through which the majority shareholder can extract benefits via tunnelling and related parties’ transactions at the expense of diverse minority shareholders. In Pakistan, there is a lack of enforcement mechanisms, a lack of insufficient minority shareholder interest protection, poor judicial efficiency, corruption and a lack of investor rights and protection (Khan et al , 2022a; Shaikh et al , 2019). Moreover, business groups affiliated firms engage in more EM than non-affiliated firms (Beuselinck and Deloof, 2014; Bhutta et al , 2016; Kim and Yi, 2006; Muttakin et al , 2017; Sun et al , 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, Lee and Kuo (2014) assert that a high proportion of managerial ownership can reduce agency costs by aligning the interests of shareholders and managers. (Khan et al ., 2022) argue that the BD and the chairman, in particular, as a mechanism of internal CG, play an essential role in preventing opportunistic behavior of management and defending shareholder rights. Thus, the control of the BD is more effective when the chairman of the board is one of the owners.…”
Section: Theoretical Literature and Hypothesis Developmentmentioning
confidence: 99%